Metabolic Profiles and Sperm Production in Imported Holstein Bull Sires under Different Climatic and Geochemical Conditions of Russia and Kazakhstan - Abilov, А. I.; Kombarova, N. A.; Amerkhanov, Kh. A.; Shemetyuk, S. A.; Shamshidin, A. S.; Mymrin, S. V.; Pyzhova, E. A.; Bogolyubova, N. V.; Gudilina, A. A.; Kombarov, S. F.; Mityashova, O. S. (Sel'skokhozyaistvennaya Biologiya. - 2021., 2021)
Currently, the potential of highly productive animals adapted to industrial farming should be used most effectively and not depend on the geographical location and agro-climatic resources of the region. Our study showed that the observation of required technologies minimizes effects of regional climatic and geochemical factors. Our findings give more understanding on the metabolic peculiarities of the sire bulls in various geo-climatic conditions of the 55.86°N and 51.18°N zone. This may be of interest for the practice of breeding the Holstein breed in countries with similar geo-climatic factors. We compared the influence of climatic and geochemical conditions of the Central Russia (the Head Center for the Reproduction of Farm Animals, Moscow Province), the Middle Urals (JSC Ural-plemcenter, Sverdlovsk Province), and the Northern Kazakhstan (RCPZh JSC Asyl-Tulik, Akmola region) on the adaptive status of the imported Holstein 3-9-year-old bull sires (n = 122). Blood levels of bioelements Ca, P, Mg, Ca:P, Fe, chlorides, Se, Cu, and Zn were recorded. To assess protein-lipid metabolism parameters and blood enzyme activity, the total protein, albumin, globulins, urea, creati-nine, total bilirubin, urea, triglycerides, cholesterol, alanine aminotransferase, aspartate aminotransfer-ase and alkaline phosphatase were measured. The endogenous hormone levels (testosterone, estradiol, thyroxine, and cortisol) were measured. The volume of ejaculate, the concentration of spermatozoa in the ejaculate, and the number of spermatozoa in the ejaculate were assessed to evaluate sperm produc-tivity. Climatic and geochemical characteristics of the regions were a temperate climate with sod-podzolic soils for the Moscow region, a sharply continental climate with bedrock rocks with sandy-clayey and sod-podzolic soils for the Middle Urals, and sever sharply continental climate with dark chestnut soil for the Northern Kazakhstan. В настоящее время потенциал высокопродуктивных животных, адаптированных к промышленному земледелию, должен использоваться максимально эффективно и не зависеть от географического положения и агроклиматических ресурсов региона. Наше исследование показало, что соблюдение необходимых технологий минимизирует влияние региональных климатических и геохимических факторов. Наши данные дают более полное представление об особенностях метаболизма быков-производителей в различных геоклиматических условиях зоны 55,86° с.ш. и 51,18° с.ш. Это может представлять интерес для практики разведения голштинской породы в странах со схожими геоклиматическими факторами. Сравнивали влияние климатических и геохимических условий Центральной России (Головной центр воспроизводства сельскохозяйственных животных, Московская обл.), Среднего Урала (ОАО «Урал-племцентр», Свердловская обл.) и Северного Казахстана (РЦПЖ, АО «Асыл- Тулик, Акмолинская область) на адаптационный статус завозных быков-производителей голштинской породы 3-9-летнего возраста (n = 122). Регистрировали уровни в крови биоэлементов Ca, P, Mg, Ca:P, Fe, хлоридов, Se, Cu и Zn. Для оценки параметров белково-липидного обмена и активности ферментов крови определяли общий белок, альбумины, глобулины, мочевину, креатинин, общий билирубин, мочевину, триглицериды, холестерин, аланинаминотрансферазу, аспартатаминотрансферазу и щелочную фосфатазу. Измеряли уровни эндогенных гормонов (тестостерон, эстрадиол, тироксин и кортизол). Для оценки спермопродукции оценивали объем эякулята, концентрацию сперматозоидов в эякуляте и количество сперматозоидов в эякуляте. Климато-геохимические характеристики регионов: умеренный климат с дерново-подзолистыми почвами для Подмосковья, резко континентальный климат с коренными породами с песчано-глинистыми и дерново-подзолистыми почвами для Среднего Урала и суровый резко континентальный климат с темно-каштановыми почвами. почвы для Северного Казахстана.
Keywords: импакт-фактор 2021; скопус; scopus; скотоводство; зарубежные авторы; научный журнал; зарубежное издание; периодическое издание; спермопродукции крс